1987
DOI: 10.1104/pp.84.4.1051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Paclobutrazol on Water Stress-Induced Abscisic Acid in Apple Seedling Leaves

Abstract: Abscisic acid (ABA) was quantitated by enzyme-linked immunosorbent assay (ELISA) in water-stressed leaves from control apple seedlings, and also from apple seedlings treated for 28 days with paclobutrazol (12RS, 3RSI-144-chlorophenyll-4,4-dimethyl-2-11,2,4-triazol-1-ylI pentan-3-ol).The ELISA quantitative estimates were also validated by gas chromatography-electron capture detector and lettuce seed germination inhibition bioassay. Paclobutrazol treatment reduced endogenous ABA levels by about one-third, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 16 publications
(16 reference statements)
0
16
0
3
Order By: Relevance
“…Recently, however, the levels of cis-abscisic acid (ABA), another plant hormone, were found to be affected by triazole applications to plants. Results have been reported that include increases in ABA levels (Lurssen 1987), a transient rise in ABA levels (Asare-Boamah et al 1986), no change (Izumi et al 1988), and decreases in ABA levels (Grossman et al 1987, Wang et al 1987. The measurements of ABA levels were reported on different species of plants and at different plant growth stages after treatment.…”
mentioning
confidence: 86%
“…Recently, however, the levels of cis-abscisic acid (ABA), another plant hormone, were found to be affected by triazole applications to plants. Results have been reported that include increases in ABA levels (Lurssen 1987), a transient rise in ABA levels (Asare-Boamah et al 1986), no change (Izumi et al 1988), and decreases in ABA levels (Grossman et al 1987, Wang et al 1987. The measurements of ABA levels were reported on different species of plants and at different plant growth stages after treatment.…”
mentioning
confidence: 86%
“…San 9785 appears to exert its actions on photosynthesis by affecting the amount and Other than carotenoid synthesis, NF has been found to inhibit ABA synthesis (38). PP333, an inhibitor of both ABA (42) and GA synthesis (7), was found to increase the level of activity of a-amylase in pea seedlings 4.6-fold (Table VII). GA is known to be required for the induction of a-amylases in certain tissues of some plant species (6).…”
Section: Localization Of A-amylase In the Apoplast Of Photobleached Amentioning
confidence: 99%
“…The possible interactions of synthetic PGRs (MEF and PBZ) in the short-term acclimation of B. rapa plants to a cold root-zone temperature was considered because of their known roles as cold protectors and their possible interaction with ABA metabolism (Asare- Boamah et al, 1986 ;Wang et al, 1987 ;Fletcher & Hofstra, 1988 ;Pardossi et al, 1992). This work was performed by pretreating plants with these PGRs (with or without an ABA pretreatment\treatment) before the acclimation to root cooling proper.…”
Section: mentioning
confidence: 99%
“…This result is not easy to interprete because the pathways of these antagonistic effects on processes involved during changes (in hydraulic conductivity and\or reflection coefficient) remained unknown. PBZ might interact with the synthesis of endogenous ABA , as shown in the leaves of apple seedlings where PBZ prevented the marked accumulation of water-stress-induced ABA that occurred in untreated control seedlings (Wang et al, 1987). Unfortunately, PBZ (like other triazole compounds) has also been reported to block GA biosynthesis by inhibiting kaurene oxidase (Fletcher & Hofstra, 1988 ;Rademacher, 1991 ;Gilley & Fletcher, 1997).…”
Section: mentioning
confidence: 99%